Student Knowledge in Reading Nutrient Label Information and Types of Packaging Food Consumed by Nursing Students - Lu'lu' Nisaa Mahmuudah; Wiwi Mardiah; Valentina BM Lumbantobing (Universitas Muhammadiyah Semarang, 2020)
Nutrient labels provided information regarding food production and lead to healthy eating. Prior health and nutrient literacy skills could support effective food label usage. Nurses needed to have good literacy skills during the education process. This study aimed to identify knowledge in reading the nutrient label and packaged food consumption in nursing students. This study used a quantitative descriptive research design. The sample was recruited from all students at the Faculty of Nursing with 42% of the response rate obtained (n= 229). Data were collected using a nutrient label questionnaire (20 items) and FFQ (83 items). Data were analyzed using a univariate method. The result showed that 55.5% of nursing students had good knowledge of reading nutrient labels. There were 5 types of processed food that most consumed by nursing students consisting of yogurt (59.8%), pudding (50.2%), chocolate bar (55.9%), cake (54.6%), and processed meatballs (54.1%). Based on the results, it can be concluded that the nutrient label knowledge of nursing students was good enough, but there needed to be an even distribution of nutrients label knowledge across the entire student stage. This can be achieved by taking several actions to increase health literacy, for instance, nutrient label booklet and nutrient label cards.